Older people’s Imaginarium about life after death - Palacios, Felipe R. Vásquez (Revista Kairós-Gerontologia, 2014)
The paper analyzes the Older people’s Imaginarium about life after death,we did a simpling worked with believers, people around over 60 years old, all thembelievers, Catholics, Methodists, Adventists and Pentecostals, who live in the Veracruzstate capital, in Mexico. The information was taked through in-depth interviews andguided discussions about the topic. Research shows the imaginary life beyond has to dowith actions and practices, cultural contexts, historical economic, religious customs thatthe company and / or individuals have accumulated in their daily lives. The centralquestion is present in all the work is: What role is playing these imaginary in the earthlylife? How to give meaning and how human life transform?